THE INFLUENCE OF RESTAURANT TAX KNOWLEDGE, TAXPAYER AWARENESS, QUALITY OF SERVICE, ADMINISTRATIVE SANCTIONS, TOTAL BILLINGS AND FINANCIAL STATEMENTS ON RESTAURANT TAX PAYING COMPLIANCE IN SUBANG CITY - Yuli Maelani; Indah Umiyati; Bambang Sugiharto (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
The purpose of this study was to determine the effect of restaurant tax knowledge, taxpayer awareness, service quality, administrative sanctions, number of bills and preparation of financial statements on compliance with paying restaurant taxes in the city of Subang. The model used is a quantitative approach. The sample in this study were restaurant entrepreneurs. The data collection instrument used primary and secondary data. Primary data was obtained by using a questionnaire or questionnaire, ordinal scale, Likert scale and ratio scale, while secondary data was obtained from the Regional Revenue Agency. The analytical method used is the validity test, reliability test, normality test and Mann Whitney test. The results of the Mann Whitney test show that the variables of restaurant tax knowledge, awareness of restaurant taxpayers, service quality, administrative sanctions, and preparation of financial statements have no effect on compliance with paying restaurant taxes, while the number of bills has a negative effect on compliance with paying restaurant taxes.